2021
DOI: 10.3389/fcell.2021.669354
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Signature of Human Embryonic Thyroid Reveals Transition From Differentiation to Functional Maturation

Abstract: The human thyroid gland acquires a differentiation program as early as weeks 3–4 of embryonic development. The onset of functional differentiation, which manifests by the appearance of colloid in thyroid follicles, takes place during gestation weeks 10–11. By 12–13 weeks functional differentiation is accomplished and the thyroid is capable of producing thyroid hormones although at a low level. During maturation, thyroid hormones yield increases and physiological mechanisms of thyroid hormone synthesis regulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 79 publications
(119 reference statements)
2
8
0
Order By: Relevance
“…[29] Transcriptomic signature comparison of human early embryonic thyroid and adult thyroid also identified cAMP signaling upregulation in adult thyroid. [11] Consistently, the dependence of adult TFC cells on the cAMP pathway has been reported by the latest study on adult mouse and human thyroid organoids. [30] However, when cAMP initiated in fetal thyroid and when subsequent cascade events occur in the narrow time window from thyroid organogenesis to functional maturation still remain elusive.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…[29] Transcriptomic signature comparison of human early embryonic thyroid and adult thyroid also identified cAMP signaling upregulation in adult thyroid. [11] Consistently, the dependence of adult TFC cells on the cAMP pathway has been reported by the latest study on adult mouse and human thyroid organoids. [30] However, when cAMP initiated in fetal thyroid and when subsequent cascade events occur in the narrow time window from thyroid organogenesis to functional maturation still remain elusive.…”
Section: Discussionsupporting
confidence: 67%
“…[ 7 , 9 ] In contrast, human studies only reported the expression pattern of specific genes in samples, [ 10 ] or the transcriptome of fetal thyroid at premature stage (7–11GWs). [ 11 ] The knowledge on the initiation of human fetal thyroid functional maturation at follicular growth stage is still limited. Recent single‐cell RNA sequencing (scRNA‐seq) of adolescent and adult zebrafish thyroid showed heterogeneity in developmental thyroid, [ 12 ] highlighting the potential of single‐cell molecular characterization in understanding thyroid maturation.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, the data show that the thyroid gland is already functional by GW11-12 (Dom et al 2021), shortly after the preplate splitting and the onset of cortical plate formation.…”
Section: Correlation Between Thyroid Function and Cortical Developmentsupporting
confidence: 55%
“…In silico prediction of Foxe1 binding motifs in up-regulated genes at the level of RNA expression and chromatin accessibility revealed 107 potential targets of Foxe1, including Pax8 and Tg (Francis-Lang et al, 1992). Other targets identified included genes involved in proper thyroid function and TSH receptor activity or deregulated in thyroid cancer, such as Lrp2/Megalin (Marinò and McCluskey, 2000), DREAM/Kcnip3 (Andrea et al, 2005), Timp3 (Zarkesh et al, 2018), Slc26a7 (Dom et al, 2021) and Bcl-2 (Fagman et al, 2011; Porreca et al, 2012). Moreover, Foxe1 binding motifs were also found in genes related to the maintenance of follicle structure, the expression of various membrane-bound transporters, and the regulation of cell-matrix adhesion.…”
Section: Discussionmentioning
confidence: 99%